Hegemoni Gaya Hidup Dan Musik Slank Dalam Membangun Loyalitas “Slankers” - Shafira, Dara; Bandiyah, Bandiyah; Ali Azhar, Muhammad (Jurnal Nawala Politika; 2019, 2019)
ABSTRACT   Slank is a band or musician who has a huge influence on his fans in Indonesia. Not many bands have as much fan base as Slank. The research entitled "Music Hegemony and Slank Lifestyle in Building Slankers' Loyalty" aims to provide an explanation of how the practice of hegemony can occur between Slank and Slankers, so that loyalty is created. This study uses descriptive qualitative research methods with in-depth interviews. The theoretical foundation used in this study is Antonio Gramsci's theory of hegemony and Michel Foucault's theory of discourse power. Based on the analysis of the data obtained the first findings, Slank managed to hegemony the Slankers through music by entering the things they want to convey through the lyrics of Slank songs and hegemony through lifestyle by convincing Slankers that Slank has the same interests as Slankers. Second, Slank has also created a power of discourse by disseminating Slank's ideology so that the Slankers will normatively justify anything that is justified by Slank.   Keywords: Hegemony, Discourse Power, Loyalty, Slank